Temporal features of erp parameters and Sensorimotor reaction during perception of "WHAT" and "WHERE" stimuli in left- and right-handers - Kachynska, Tetiana V.; Kuznietsov, Illia P.; Kotsan, Ihor Ya.; Kozachuk, Nataliia O.; Abramchuk, Olha M.; Качинська, Тетяна Володимирівна; Кузнєцов, Ілля Павлович; Коцан, Ігор Ярославович; Козачук, Наталія Олександрівна; Абрамчук, Ольга Миколаївна (Київський національний університет ім. Тараса Шевченка, 2016)
The temporal features of ERP components and sensorimotor reaction during the perception of "What" and "Where" stimuli in left- and right-handers were studied. We suppose, that asymmetry type affects the time characteristics of ERP components and sensorimotor reaction. During the first test left-handers had shorter latencies of ERP components on all perception stages. Moreover, latencies of P3 and N3 components in frontal, central, parietal and occipital areas of both hemispheres in left-handers were statistically significantly shorter, in comparison with right-handers. During the second test the similar dynamic was observed, but statistical differences wasn’t detected. Thus, the temporal ERP characteristics are sensitive to human individual features, such as manual asymmetry.
Keywords: right-handers; left-handers; manual asymmetry; ERP components; sensorimotor reaction; latencies